BERPIJAK DI BUMI – BERPIHAK KEPADA MANUSIA (Mandat dari Gaudium et Spes) - Paul Budi Kleden (Institut Filsafat dan Teknologi Kreatif Ledalero, 2013)
Gaudium et Spes is a revolutionary document of Vatican II which can still inspire the Church now and in the future. This document is revolutionary in the sense that it deals with problems, issues and ideas that had never before become the agenda of any Council in the Catholic Church. Gaudium et Spes concretizes what John XXIII named aggiornamento, a process of contextualising the Christian heritage, through which the Church opens itself up to the modern world. This document is also revolutionary because it is entirely a product of the conciliar process of the Council itself. This article presents the process of drafting the document and discusses some issues that are relevant for the Church today and in the future. Kata-kata kunci: proses, Gereja, dunia modern, solidaritas, keadilan ekonomi, martabat manusia, perdamaian.